Do human beings have a tail? - Mohammed Hamada Takrouney; Omnia Hussein Thabet; Mohamed Abdelkader Osman; Hala Saad Abdel-Ghaffar; Mahmoud Mohamed Mostafa (Elsevier, 2023)
Human tail is an established caudal body anomaly. Having a baby with a tail causes emotional and social burden on the family. Embryological development explanation of human tail makes its management feasible and easy. Early detection and surgical consultation is the key for proper treatment and we have to present suitable social orientations concerning these intriguing rare cases. We reported a case of male infant one-month old with pseudo-human tail treated with surgical excision with smooth postoperative sequelae.